Between Absorption, Abstraction and Exhibition: Inflections of the Cinematic Tableau in the Films of Corneliu Porumboiu, Roy Andersson and Joanna Hogg - Pethő Ágnes (Acta Universitatis Sapientiae: Film and Media Studies, 2015)
The paper proposes to focus on the multiple affordances and intermedial aesthetic of the cinematic tableau seen as a performative space resulting in the impression of watching a painting, a theatre stage, a shop window, a diorama, or a photo-filmic installation in which the play between stillness and motion is accompanied by a reflexive emphasis on media and the senses. Such images, described extensively by David Bordwell in his writings on the evolution of film style, are being re-evaluated through debates on the “tableau form,” “absorption and theatricality” in modern art and photography (e.g. Jean-François Chevrier, Michael Fried). In particular, the aim of this paper is to examine inflections of the cinematic tableau in the films of three contemporary European authors, Corneliu Porumboiu (Romania), Roy Andersson (Sweden) and Joanna Hogg (UK), and relate them to the paradigm of the Dutch interior established in seventeenth-century painting.